Laparoscopic versus open nephroureterectomy for upper urinary tract urothelial carcinoma: A systematic review and meta-analysis. Issue 35 (August 2018) - Liu, Feng; Guo, Wei; Zhou, Xueying; Ding, Youpeng; Ma, Yanan; Hou, Yi; Kong, Xiangbo; Wang, Zhixin
Abstract: Purpose: To evaluate the efficacy and safety of laparoscopic nephroureterectomy (LNU) and open nephroureterectomy (ONU) for the treatment of upper urinary tract urothelial carcinoma (UTUC). Methods: PubMed, Embase, and Cochrane databases were selected for systematic review of trials that compared outcomes of LNU and ONU. Meta-analysis was performed using RevMan 5.3 and STATA 13.0 software. Results: LNU was associated with longer operation time ( P <  .001), shorter hospital stay ( P <  .001), less blood loss ( P =  .006) and lower rate of transfusion ( P <  .001). The occurrence of complications, including minor ( P =  .52), major ( P =  .21) and total complications ( P =  .19) were similar between LNU and ONU. There was no significant difference in the rate of 5-year recurrence-free survival ( P =  .90), 5-year cancer-specific survival ( P =  .12), and 5-year overall survival ( P =  .11) as well as 2-year RFS ( P =  .84), 2-year CSS ( P =  .86), and 2-year OS ( P =  .25). Conclusion: Our results indicated that LNU is a safe and effective method to treat UTUC. Given the limitations of this study, further multicenter, randomized trials are required to confirm these findings.